2020
DOI: 10.1007/s11869-020-00870-2
|View full text |Cite
|
Sign up to set email alerts
|

Gauging the air quality of New York: a non-linear Nexus between COVID-19 and nitrogen dioxide emission

Abstract: The primary objective of the study is to analyse the relationship between COVID-19 and nitrogen dioxide in New York City during the global pandemic. Notably, the study has investigated the direct influence of lockdown circumstances (due to COVID-19) and plunge in the population of New York on its environmental contamination. The study utilized the Non-Linear Autoregressive Distributed Lag (NARDL) model to ascertain the asymmetric impact of COVID-19 on the environmental quality of the USA. The results reveal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…It vehemently rejects the null hypothesis of no cointegration (F-statistics < lower bound critical value). F-statistics significance at a 1% level confirms the cointegration occurrence for a long-run relationship between CO 2 emission and COVID-19 with its determinants (Katrakilidis & Trachanas, 2012 ; Sarfraz et al, 2018 , 2020 ; Zhang et al, 2017 ).…”
Section: Resultsmentioning
confidence: 65%
“…It vehemently rejects the null hypothesis of no cointegration (F-statistics < lower bound critical value). F-statistics significance at a 1% level confirms the cointegration occurrence for a long-run relationship between CO 2 emission and COVID-19 with its determinants (Katrakilidis & Trachanas, 2012 ; Sarfraz et al, 2018 , 2020 ; Zhang et al, 2017 ).…”
Section: Resultsmentioning
confidence: 65%
“…Many countries have imposed lockdown policies to close schools, workplace, public transport, and their international borders. It has been reported that these lockdown policies have brought some positive impacts towards the environment at the city or country level ( Filonchyk et al, 2020 ; Lau et al, 2020 ; Sarfraz et al, 2020 ; Siddiqui et al, 2020 ; Tobias et al, 2020 ). This study evaluated these impacts of COVID-19 pandemic towards the global NO 2 dynamics based on data from 187 countries/regions.…”
Section: Resultsmentioning
confidence: 99%
“…The whole country became unusually quiet in February, which has always been a peak travelling season due to the Chinese New Year. The lockdowns of cities have been widely reported to bring significant positive impacts towards the environment, particularly on air quality, including sulfur dioxide (SO 2 ), nitrogen dioxide (NO 2 ) and fine particles (PM 2.5 ) ( Filonchyk et al, 2020 ; Lancet Planet Health, 2020 ; Lau et al, 2020 ; Le Quere et al, 2020 ; Sarfraz et al, 2020 ; Tobias et al, 2020 ; Wang and Wang, 2020 ; Zhao et al, 2020 ). As the anthropogenic NO 2 is highly related to fossil fuel combustion from various transport modes, including vehicular traffic, marine shipping and commercial aircraft, the quarantine policies have resulted in a significant drop of NO 2 between late January and early March 2020 by 22.8 μg/m 3 in Wuhan alone and 12.9 μg/m 3 for the whole of China ( Agudelo-Castaneda et al, 2020 ; Herndon et al, 2004 ; Kaminska, 2019 ; Lancet Planet Health, 2020 ; Liu et al, 2020 ; Wang and Su, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, Pata (2020) studied the impact of COVID-19 pandemic on environmental pollution in eight different US cities and found that the ongoing pandemic decreased the PM 2.5 emission in the US. Similarly, Sarfraz et al (2020) investigated the relationship between COVID-19 and NO 2 concentration level in New York City and revealed that environmental quality significantly improved during the pandemic. Moreover, Agarwal et al (2020) analyzed the influence of lockdown measures on air pollution of six megacities of India and six cities in China and concluded that air pollution in considered cities reduced drastically.…”
Section: Introductionmentioning
confidence: 99%